2012
DOI: 10.1002/ppap.201200023
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymerization of a Saturated Branched Hydrocarbon. The Case of Heptamethylnonane

Abstract: 2,2,4,4,6,8,8‐Heptamethylnonane (HMN), a saturated branched hydrocarbon precursor, is deposited by means of atmospheric plasma DBD. Hydrophobic coatings starting from this precursor which is liquid at room temperature can be obtained. The degree of polymerization of the coating seems to be dependent on the amount of provided precursor. The coatings were characterized by FTIR, TOF‐SIMS, WCA, SE, and XPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
4
5
0
Order By: Relevance
“…This may suggest that the ion‐assisted etching is predominant in this domain, where the ablation process causes a significant reduction of deposition rate. A drop in deposition rate at higher specific energies has also been previously observed for other monomers . In the energy‐sufficient domain the deposition rate levels off and remains relatively constant by the increasing W / F ratios, indicating that the equilibrium between ablation and deposition processes is reached.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This may suggest that the ion‐assisted etching is predominant in this domain, where the ablation process causes a significant reduction of deposition rate. A drop in deposition rate at higher specific energies has also been previously observed for other monomers . In the energy‐sufficient domain the deposition rate levels off and remains relatively constant by the increasing W / F ratios, indicating that the equilibrium between ablation and deposition processes is reached.…”
Section: Resultssupporting
confidence: 72%
“…The deposition rate over 0–60 min of polymerisation time, estimated from the slope of the linear trend line, is ≈2.7 nm · min −1 . Such a linear increase of film thickness with polymerisation time is well documented in the literature …”
Section: Resultssupporting
confidence: 67%
“…6. Such a linear increase was expected and is consistent with the reported data in the literature for other monomers [20,50,58]. From this data, a deposition rate of ≈6.3 nm.min −1 is estimated for the plasma polymerization of thiophene on silicon wafers.…”
Section: Deposition Rate Of Ppt Coating On Particulate and Planar Sursupporting
confidence: 82%
“…These changes in surface chemistry may suggest the predominance of an ablation mechanism which etches the deposited fragments off the surface. Such behaviour is known as competitive ablation and polymerization (CAP) [21] and has also been observed for other plasma polymers deposited at relatively high W/F ratios [48][49][50]. According to the XPS data, it can be concluded that the optimal plasma polymerization of thiophene on silica particles is achieved at a W/F of approximately 0.08 kJ ⋅ cm − 3 , where the maximum concentration of sulfur is obtained on the surface.…”
Section: Influence Of Plasma Polymerization Energy On Surface Chemistrymentioning
confidence: 80%
“…However, the concentration of middle-sized fragments in the active volume of the discharge during plasma deposition of AMA (C 3 H 5 þ and C 4 H 5 O þ ) and PiB (C 3 H 7 þ and C 4 H 7 O þ ) both tended to decrease. In literature, the chemical analysis of thin plasma films based on FTIR, XPS, [15,16] solid state 13 C NMR, [17] optical emission spectroscopy (OES), [18] electron spin resonance spectroscopy (ESR), [19,20] mass spectrometry, [21] and secondary ion mass spectroscopy (SIMS) [22][23][24] is predominant.…”
Section: Introductionmentioning
confidence: 99%